Implementation of the Pancasila Student Profile Strengthening Project Module (P5) on Elementary School Student’s Creativity: An Experimental Study - Sri Ramadhani; Azizah; Nurjannah; Lhutfia Wahyu Safutri (Universitas Pendidikan Ganesha, 2025)
The Pancasila Student Profile Strengthening Project (P5) implemented at SD Inpres Bumi Sagu only uses textbooks. This study aims to determine the implementation of the P5 module on students' creativity at SD Inpres Bumi Sagu. This type of research is an experimental study with a Pre-Experimental Design research design in the form of a pre-test and post-test one-group design. The subjects of this study were 30 students of phase B, grade IV of SD Inpres Bumi Sagu. The research instrument used was a questionnaire. Data analysis used a paired sample t-test assisted by the SPSS Statistics version 29 program. Based on the results of the study, a significance value of 0.001 <0.05 was obtained. The hypothesis Ha was accepted and Ho was rejected, which means that the P5 Module is effective in improving students' creativity. So it can be concluded that the P5 Module effectively improves the creativity of grade IV students at SD Inpres Bumi Sagu.